Influence of the rolling of contact pads on crack initiation in fretting fatigue tests. (October 2022) - Erena, Diego; Martín, Vicente; Vázquez, Jesús; Navarro, Carlos
Highlights: Fretting fatigue contact stress analysis when small rolling occurs in the pad. Experimental contact semi-width is larger than the theoretical one due to rolling. Rolling effect modify substantially contact stress/strain fields and initial crack path. Abstract: This work performs a detailed analysis of the cracks obtained in fretting fatigue tests with cylindrical contact in the presence of a small oscillatory rolling of the contact pad. To do so, fretting fatigue tests have been carried out. Preliminary observations indicate that the contact area is larger than the theoretical one according to Hertz's theory. This could mean that, due to the contact geometry and the stiffness of the test setup, rolling of the contact pad is occurring during tests. To reproduce this phenomenon, a 2D numerical model is developed. The results are compared with actual crack profile measurements.